High-aluminum heat-resistant steel welding wire for thermal power plant and preparation method
By preparing high-alumina heat-resistant steel welding wire, an austenitic + ferrite microstructure is formed and a dense oxide film is formed on the weld surface. This solves the problem of grain coarsening and high-temperature performance mismatch in high-alumina ferritic heat-resistant steel welds, improves the high-temperature performance and oxidation resistance of the weld, and reduces costs.
Patent Information
- Application Number
- CN202511507450.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-21
- Publication Date
- 2025-11-28
AI Technical Summary
The existing high-alumina ferritic heat-resistant steel welds suffer from severe grain coarsening and mismatch between high-temperature performance and base material. Traditional welding materials cannot effectively transfer aluminum, resulting in decreased weld toughness and insufficient oxidation resistance.
A high-alumina heat-resistant steel welding wire for thermal power plants is designed, which contains a specific composition of flux powder and 430 steel strip. It is prepared by heating, mixing and drawing processes to form an austenitic + ferrite structure and a dense Al2O3-Cr2O3-rare earth oxide composite film on the weld surface, which synergistically improves the high-temperature performance of the weld.
It achieves a match between the thermal expansion coefficient and thermal conductivity of the weld and the base material, reduces residual welding stress, avoids thermal fatigue cracks, significantly improves the high-temperature oxidation resistance and strength of the weld, and reduces costs.
Smart Images

Figure CN121017922A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure belongs to the technical field of metal materials, and particularly relates to a high-aluminum type heat-resistant steel welding wire for a thermal power plant and a preparation method. BACKGROUND
[0002] With the transformation of global energy structure towards high efficiency and low carbon, key components such as boilers and steam pipes of thermal power plants are developing towards ultra-supercritical (USC) and advanced ultra-supercritical (A-USC) parameters, and the continuous improvement of working temperature (600-650℃) and pressure (more than 30MPa) puts forward more stringent requirements for heat-resistant steel materials. Although the traditional austenitic heat-resistant steel (such as Super304H and HR3C) has excellent high-temperature strength, its high nickel content leads to high cost, and its high thermal expansion coefficient and poor thermal conductivity easily cause thermal fatigue cracks under frequent start-stop conditions. Under this background, high-aluminum type austenitic ferritic heat-resistant steel has become a potential alternative material for high-temperature components of thermal power plants due to its low thermal expansion coefficient, excellent steam oxidation resistance and good thermal conductivity. However, the weldability problem of this type of steel seriously restricts its engineering application. (1) Welding metallurgy problems: 1) Aluminum oxidation problem: aluminum is easily oxidized to form Al2O3 inclusions under the high temperature of electric arc, which leads to the decrease of plasticity and toughness of the weld, and may cause defects such as pores and slag; 2) Ferrite coarsening tendency: high aluminum content inhibits austenite transformation, and the weld shows full ferrite structure, which rapidly grows under high-temperature thermal cycle and deteriorates the creep resistance; 3) Alloy element transition difficulty: traditional welding wire (such as ER430) cannot effectively transition aluminum element, which leads to the mismatch of composition between the weld and the base material, and insufficient oxidation resistance.
[0003] (2) Limitations of existing welding materials: 1) Ordinary ferritic steel welding wire (such as ER446) has low aluminum content, which cannot form a continuous Al2O3 protective film, and cannot meet the demand of USC boiler high-temperature steam oxidation environment; 2) Nickel-based welding materials (such as ERNiCr-3) can weld dissimilar materials, but the cost is high and the thermal expansion coefficient is not matched, which easily leads to interface failure due to stress concentration in long-term service.
[0004] In view of the above problems, the present disclosure provides a high-aluminum type heat-resistant steel welding wire for a thermal power plant, which breaks through the core material problem of USC / A-USC unit, and provides key technical support for building a clean, efficient and safe modern energy system. SUMMARY
[0005] The present disclosure aims to at least solve one of the technical problems of the prior art, i.e., the serious grain coarsening of the high-aluminum ferritic heat-resistant steel weld, and the mismatch between the high-temperature performance and the base material, and provides a high-aluminum heat-resistant steel welding wire for a thermal power plant and a preparation method thereof.
[0006] In one aspect of the present disclosure, a high-aluminum heat-resistant steel welding wire for a thermal power plant is provided, the welding wire comprising: a powder and a sheath, wherein, The powder comprises the following components in percentage by mass: Mn 40.0-50.0%, Al 10.0-12.0%, Cr 15.0-20.0%, Si 6.0-10.0%, Nb 1.0-3.0%, B 0.6-1.0%, Ti 0.8-1.2%, C 0.8-1.2%, Ce 1.0-1.5%, and the rest is Fe. The sheath is a 430 steel strip.
[0007] Optionally, the particle size of the powder is 100-200 mesh.
[0008] Optionally, the filling rate of the powder is controlled to be 22-25%.
[0009] Optionally, the thickness of the 430 steel strip is 0.3-0.5 mm, and the width is 6-8 mm.
[0010] In another aspect of the present disclosure, a method for preparing the high-aluminum heat-resistant steel welding wire for a thermal power plant described above is provided, the method comprising: Mn 40.0-50.0%, Al 10.0-12.0%, Cr 15.0-20.0%, Si 6.0-10.0%, Nb 1.0-3.0%, B 0.6-1.0%, Ti 0.8-1.2%, C 0.8-1.2%, Ce 1.0-1.5%, and the rest is Fe, are weighed in percentage by mass as a powder; The powder is subjected to a heat treatment, and the treated powder is mixed; The sheath is pretreated, and the mixed powder is wrapped in the 430 steel strip of the sheath, and is subjected to a drawing treatment to obtain the high-aluminum heat-resistant steel welding wire for a thermal power plant.
[0011] Optionally, the temperature for the heat treatment of the powder is 200-230°C, and the holding time is 1-2 h.
[0012] Optionally, the mixing time of the treated powder is 1-2 h.
[0013] Optionally, the diameter of the high-aluminum heat-resistant steel welding wire for a thermal power plant is 1.0-1.2 mm.
[0014] The high-aluminum type heat-resistant steel welding wire for thermal power plants can be applied to butt welding of 2Mn18Al5SiMoTi test plates.
[0015] Alternatively, the high-aluminum type heat-resistant steel welding wire for thermal power plants forms a dense Al2O3-Cr2O3-rare earth oxide composite film on the weld surface in butt welding of 2Mn18Al5SiMoTi test plates.
[0016] The high-aluminum type heat-resistant steel welding wire for thermal power plants and a preparation method thereof are provided. The welding wire comprises: a powder and a sheath, wherein the powder comprises the following components in percentage by mass: Mn 40.0-50.0%, Al 10.0-12.0%, Cr 15.0-20.0%, Si 6.0-10.0%, Nb 1.0-3.0%, B 0.6-1.0%, Ti 0.8-1.2%, C 0.8-1.2%, Ce 1.0-1.5%, and the rest is Fe; and the sheath is a 430 steel belt. The welding wire has a simple preparation process and excellent high-temperature performance of the obtained weld. Through the synergistic regulation of various elements, an austenite + ferrite structure is formed. Through Al, Cr and Ce rare earth elements, a dense Al2O3-Cr2O3-rare earth oxide composite film is formed on the weld surface, significantly improving the high-temperature performance of the weld metal, and solving the problems of existing high-aluminum type ferrite heat-resistant steel welds, such as serious grain coarsening, high-temperature performance mismatching with the base material, and the like. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 The flowchart of the preparation method of the high-aluminum type heat-resistant steel welding wire for thermal power plants is shown in the specific embodiment of the present disclosure. Figure 2 The scanning electron microscope structure of the butt joint weld prepared in Example 2 of the present disclosure is shown. Figure 3 The tensile fracture morphology of the butt joint prepared in Example 2 of the present disclosure is shown. DETAILED DESCRIPTION
[0018] In order for those skilled in the art to better understand the technical solutions of the present disclosure, the present disclosure will be further described in detail below in combination with the drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, but not all embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present disclosure.
[0019] In one aspect of the present disclosure, a high-aluminum heat-resistant steel welding wire for a thermal power plant is provided, which comprises: a powder and a welding sheath, wherein the powder comprises the following components in percentage by mass: Mn 40.0-50.0%, Al 10.0-12.0%, Cr 15.0-20.0%, Si 6.0-10.0%, Nb 1.0-3.0%, B 0.6-1.0%, Ti 0.8-1.2%, C 0.8-1.2%, Ce 1.0-1.5%, and the balance being Fe, and the sum of the above component percentages is 100%; and the welding sheath is a 430 steel strip.
[0020] In some preferred embodiments, the purity of each of the above raw material component alloy powders is ≥99.9%, and the particle size of the above metal powder is 100-200 mesh.
[0021] In some preferred embodiments, the filling rate of the powder is controlled to be 22-25%.
[0022] The welding wire of the present embodiment is designed mainly for a high-aluminum heat-resistant steel base material (such as 2Mn18Al5SiMoTi), and the Al (10-12%) and Cr (15-20%) elements in the powder are close to the composition of the base material, so as to reduce the risk of interface failure caused by composition difference. The thermal expansion coefficient and thermal conductivity of the dual-phase structure (austenite + ferrite) match those of the base material, so as to reduce the welding residual stress and avoid thermal fatigue cracks.
[0023] The functions of the main alloy components of the welding wire designed in the present embodiment are as follows: (1) The welding wire cladding metal contains a certain amount of Cr element: Cr is a ferrite-forming element, and the addition of Cr helps to form a small amount of high-temperature ferrite phase. Cr can form a dense Cr2O3 oxide at high temperature, which ensures the high-temperature oxidation resistance of the cladding metal. The Cr2O3 oxide forms a composite oxide protective film with Al2O3 and rare earth oxides, which significantly prolongs the service life of the boiler pipe.
[0024] (2) The welding wire cladding metal contains a certain amount of Mn: Mn is an austenite-forming element, and the addition of Mn can form a certain amount of austenite structure in the weld, which balances the problems of grain coarsening and hot working performance caused by full ferrite structure. As can be seen from the Fe-Al-Mn ternary phase diagram, when the content of Mn is too high, Mn and Al have the possibility of forming a brittle β-Mn phase. The present invention controls the addition amount of Mn to be 40.0-50.0%.
[0025] (3) The welding wire cladding metal contains a certain amount of Al: Al forms Al2O3 at high temperatures, which can protect the weld metal. The oxidation resistance of 6% Al content is comparable to that of 18% Cr. Therefore, adding a certain amount of Al to the weld can reduce the addition of Cr content while ensuring high-temperature performance. That is, the Al element disclosed in this invention can improve the high-temperature performance and high-temperature strength of the weld metal. Excessive Al content will affect arc stability and result in greater spatter. Therefore, the amount of Al added in this invention is controlled at 10.0~12.0%.
[0026] (4) The welding wire cladding metal contains a certain amount of Nb: As a key microalloying element, Nb significantly improves the comprehensive performance of the weld metal through multiple mechanisms. When it dissolves in the austenitic matrix, it induces lattice distortion, effectively hindering dislocation movement and thus enhancing the high-temperature strength of the material. At the same time, Nb can significantly improve the corrosion resistance of γ-Fe, especially enhancing the resistance to intergranular corrosion. As a strong carbide-forming element, Nb preferentially combines with carbon to form stable NbC particles. These fine precipitates can effectively pin grain boundaries and inhibit high-temperature grain growth. In addition, Nb also exhibits ferrite stabilization characteristics and works synergistically with Cr to promote the formation of high-temperature ferrite phase. However, it is necessary to control the Nb content within the range of 1.0~3.0% to avoid excessive ferrite phase damaging the plasticity and toughness of the material. This multi-effect synergistic effect makes Nb an ideal alloying element for optimizing the microstructure and properties of heat-resistant steel welds.
[0027] (5) The cladding metal of the welding wire contains a certain amount of Si: Silicon (Si), as a ferrite stabilizing element, plays multiple key roles in austenitic stainless steel. Its addition can not only significantly improve the material's resistance to high-temperature oxidation, but also form an efficient joint deoxidation mechanism in synergy with manganese (Mn). During the welding process, Si and Mn effectively reduce the oxygen content in the molten pool through chemical reaction, thereby reducing the number of oxide inclusions and significantly improving the comprehensive performance of the weld metal. However, the Si content must be strictly controlled. When it exceeds 3%, it will lead to the deterioration of the material's hot working performance and cause high-temperature aging embrittlement. Based on this, the present invention optimizes and controls the amount of Si added in the flux powder within the range of 6.0~10.0%, ensuring that the actual Si content in the cladding metal is maintained in the ideal range of 1.32~2.5%, thus ensuring the deoxidation effect while avoiding negative impacts on the material's performance. This precise composition control achieves the best balance between deoxidation efficiency and material ductility and toughness.
[0028] (6) The welding wire cladding metal contains a certain amount of Ti element: Ti plays a similar role to Nb in the weld. Ti is a strong carbide forming element and preferentially combines with C to form TiC, which refines the grains and prevents grain boundary migration at high temperatures.
[0029] (7) The welding wire cladding metal contains a small amount of boron (B): As an interstitial solid solution element, boron can dissolve in iron cells, thereby effectively improving the high-temperature strength of the weld metal. Boron segregates at grain boundaries, which can improve the bonding strength of grain boundaries and the creep resistance of the weld metal at high temperatures. Excessive boron content will form a brittle Fe-B phase, so the addition of boron in the flux powder is controlled at 0.6~1.0%.
[0030] (8) The welding wire cladding metal contains a certain amount of carbon (C): In austenitic structures, carbon (C) exhibits significantly higher solid solution capacity than ferrite and martensite, mainly strengthening the weld metal through interstitial solid solution mechanisms. As an austenite stabilizing element, C can effectively promote the formation and stabilization of the austenite main phase. At the same time, C reacts with elements such as Nb and Ti added to the alloy to generate fine NbC and TiC carbides. These nanoscale precipitates effectively inhibit the coarsening and growth of austenite grains under high-temperature conditions through grain boundary pinning mechanisms. However, it is necessary to control the C content within the optimized range of 0.8% to 1.2%. Excessive C content will not only impair arc stability but may also adversely affect welding process performance. This precise control of carbon content achieves the best balance between material strengthening, microstructure stability, and process feasibility.
[0031] (9) Rare earth element Ce is added to the welding wire: In low-nickel or nickel-free alloy systems, the addition of rare earth element Ce can effectively compensate for the adverse effects of reduced nickel content on the high-temperature performance of the weld. Ce significantly improves the high-temperature stability of the weld metal through the mechanism of purifying grain boundaries and enhancing grain boundary bonding strength. Ce rare earth element, together with Al and Cr elements, forms a dense Al2O3-Cr2O3-rare earth oxide composite film on the weld surface, which significantly extends the high-temperature life of the weld. In addition, the introduction of trace amounts of Ce can also optimize the discharge characteristics of the welding arc and ensure the continuous stability of arc combustion. This not only improves the welding process performance, but also makes the final weld surface more uniform and beautiful.
[0032] In some other preferred embodiments, the thickness of the 430 steel strip is 0.3-0.5 mm, for example, preferably 0.4 mm, and the width is 6-8 mm, for example, preferably 7 mm. The design of the weld skin thickness (0.4 mm) and filler content (22-25%) ensures that the flux is evenly coated during the drawing process, preventing flux leakage or uneven distribution, and ensuring the consistency of the weld composition.
[0033] The welding skin in this embodiment uses 430 steel strip (ferritic stainless steel), whose high chromium content (about 16-18%) is compatible with the alloy components (such as Cr, Al, etc.) in the welding wire powder, and can effectively protect the powder from excessive oxidation during the welding process.
[0034] Furthermore, the chromium (Cr) in the weld bead works synergistically with elements such as Al, Cr, and Si in the flux powder to form a dense composite oxide protective film (such as Al2O3-Cr2O3) in the weld, enhancing its high-temperature oxidation resistance. The weld bead, acting as a ferrite-forming carrier, works with austenite-forming elements (such as Mn) in the flux powder to regulate the austenite + ferrite dual-phase structure of the weld, avoiding the hot brittleness of pure ferrite or the hot cracking tendency of pure austenite.
[0035] As shown in Figure 1, another aspect of this disclosure provides a method S100 for preparing high-alumina heat-resistant steel welding wire for thermal power plants, specifically including the following steps S110~S130: S110: Weigh out the following components by mass percentage: Mn 40.0~50.0%, Al 10.0~12.0%, Cr 15.0~20.0%, Si 6.0~10.0%, Nb 1.0~3.0%, B 0.6~1.0%, Ti 0.8~1.2%, C 0.8~1.2%, Ce 1.0~1.5%, with the remainder being Fe. The sum of the mass percentages of the above components is 100%, and this is used as the pharmaceutical powder. S120. Place the weighed medicine powder from step 1 into a vacuum heating furnace and heat it at a temperature of 200~230℃ for 1~2 hours to remove the water of crystallization from the medicine powder. After drying, place the medicine powder into a powder mixer for thorough mixing for 1~2 hours.
[0036] S130. Use alcohol to remove the grease from the surface of the 430 steel strip. Use a flux-cored wire drawing device to wrap the flux powder prepared in step S120 inside the 430 steel strip. The diameter of the first drawing die is 2.6mm.
[0037] In step S130, after the first drawing process is completed, the die aperture is reduced sequentially to finally obtain flux-cored welding wire with a diameter of 1.0~1.2mm. In addition, it should be noted that after the flux-cored welding wire is drawn, it should be wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use.
[0038] This disclosure proposes a high-alumina heat-resistant steel welding wire for thermal power plants that can be used for butt welding of 2Mn18Al5SiMoTi test plates. Furthermore, during butt welding of 2Mn18Al5SiMoTi test plates using this high-alumina heat-resistant steel welding wire, a dense Al2O3-Cr2O3-rare earth oxide composite film is formed on the weld surface.
[0039] It should be understood that the Al2O3-Cr2O3-rare earth oxide composite film formed on the weld surface has a similar structure to the oxide film of the substrate, and they synergistically resist oxidation in a high-temperature steam environment. At the same time, microalloying elements (Nb, Ti, B) refine the grains and pin the grain boundaries, inhibiting high-temperature grain coarsening, so that both the weld and the substrate maintain high strength and toughness at high temperatures. The dual-phase structure (austenite + ferrite) matches the coefficient of thermal expansion and thermal conductivity of the substrate, reducing welding residual stress and avoiding thermal fatigue cracks.
[0040] The following will further illustrate the high-alumina heat-resistant steel welding wire for thermal power plants and its preparation method with specific embodiments: Example 1 This example illustrates the high-alumina heat-resistant steel welding wire for thermal power plants and its preparation method, including the following steps: Step 1: Weigh out the following components by mass percentage: Mn 40.0%, Al 10.0%, Cr 15.0%, Si 6.0%, Nb 1.0%, B 0.6%, Ti 0.8%, C 0.8%, Ce 1.0%, and the remainder Fe. The sum of the mass percentages of the above components is 100%.
[0041] Step 2: Place the powder weighed in Step 1 into a vacuum heating furnace and heat it at 200℃ for 1 hour to remove the water of crystallization from the powder; place the dried powder into a powder mixer for thorough mixing for 1 hour. Step 3: Use alcohol to remove the grease from the surface of the 430 steel strip, and use a flux-cored wire drawing device to wrap the flux powder prepared in step 2 inside the 430 steel strip. The diameter of the first drawing die is 2.6mm. Step 4: After the first drawing process is completed, the die hole diameter is reduced in sequence to finally obtain flux-cored welding wire with a diameter of 1.0~1.2mm.
[0042] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use.
[0043] The welding wire prepared in Implementation Case 1 was used for butt welding of 2Mn18Al5SiMoTi test plates. After welding, metallographic observation specimens, tensile specimens, and high-temperature corrosion specimens were prepared. The test results are as follows: (1) The metallographic structure of the weld metal is a dual-phase structure of austenite + ferrite.
[0044] (2) The room temperature tensile test was carried out in accordance with GB / T 228.1-2021 "Metallic materials, tensile test - Part 1: room temperature test method". The test results showed that the room temperature tensile strength of the welded joint was 724 MPa.
[0045] (3) The high temperature tensile test was carried out in accordance with GB / T 4338-2006 "Metallic Materials High Temperature Tensile Test Method". The test results showed that the high temperature tensile strength of the welded joint at 500℃ was 431MPa.
[0046] (4) A high-temperature corrosion test at 400℃ was conducted in accordance with GB / T 38430-2019 "Corrosion of metals and alloys - Isothermal exposure oxidation test method for metallic materials under high temperature corrosion conditions". A comparative test was conducted using 3Cr24Ni7SiNRE stainless steel. The test results showed that the high-temperature oxidation resistance of the cladding metal of the present invention is 1.8 times that of the base material 2Mn18Al5SiMoTi.
[0047] Example 2 Step 1: Weigh out the following components by mass percentage: Mn 50.0%, Al 12.0%, Cr 20.0%, Si 10.0%, Nb 3.0%, B 1.0%, Ti 1.2%, C 1.2%, Ce 1.5%, with the remainder being Fe. The sum of the mass percentages of the above components is 100%.
[0048] Step 2: Place the weighed powder from Step 1 into a vacuum heating furnace and heat it at 230℃ for 2 hours to remove the water of crystallization from the powder; place the dried powder into a powder mixer for thorough mixing for 2 hours. Step 3: Use alcohol to remove the grease from the surface of the 430 steel strip, and use a flux-cored wire drawing device to wrap the flux powder prepared in step 2 inside the 430 steel strip. The diameter of the first drawing die is 2.6mm. Step 4: After the first drawing process is completed, the die hole diameter is reduced in sequence to finally obtain flux-cored welding wire with a diameter of 1.0~1.2mm.
[0049] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use.
[0050] The welding wire prepared in Implementation Case 2 was used for butt welding of 2Mn18Al5SiMoTi test plates. After welding, metallographic observation specimens, tensile specimens, and high-temperature corrosion specimens were prepared. The test results are as follows: (1) The metallographic structure of the weld metal is a dual-phase structure of austenite + ferrite.
[0051] (2) The room temperature tensile test was carried out in accordance with GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Room temperature test method". The test results showed that the room temperature tensile strength of the butt joint was 737 MPa.
[0052] (3) The high temperature tensile test was carried out in accordance with GB / T 4338-2006 "Metallic Materials High Temperature Tensile Test Method". The test results showed that the tensile strength of the butt joint at 500℃ was 438MPa.
[0053] (4) A high-temperature corrosion test at 400℃ was conducted in accordance with GB / T 38430-2019 "Corrosion of metals and alloys - Isothermal exposure oxidation test method for metallic materials under high temperature corrosion conditions". A comparative test was conducted using 3Cr24Ni7SiNRE stainless steel. The test results showed that the high-temperature oxidation resistance of the cladding metal of the present invention was 1.98 times that of the base material 2Mn18Al5SiMoTi.
[0054] Figure 2 The image shows the scanning electron microscope (SEM) microstructure of the butt joint weld prepared using Example 2. As can be seen from the figure, the weld microstructure consists of austenite and ferrite, consistent with the design objectives.
[0055] Figure 3 The tensile fracture morphology of the butt joint prepared using Implementation Case 2 is shown in the figure. As can be seen from the figure, the tensile fracture surface of the weld has a lot of toughness, indicating good toughness.
[0056] Example 3 Step 1: Weigh out the following components by mass percentage: Mn 45.0%, Al 11.0%, Cr 18.0%, Si 8.0%, Nb 2.0%, B 0.8%, Ti 1.0%, C 1.0%, Ce 1.3%, with the remainder being Fe. The sum of the mass percentages of the above components is 100%.
[0057] Step 2: Place the weighed powder from Step 1 into a vacuum heating furnace and heat it at 215℃ for 1.5 hours to remove the water of crystallization from the powder. After drying, place the powder into a powder mixer for thorough mixing for 1.5 hours. Step 3: Use alcohol to remove the grease from the surface of the 430 steel strip, and use a flux-cored wire drawing device to wrap the flux powder prepared in step 2 inside the 430 steel strip. The diameter of the first drawing die is 2.6mm. Step 4: After the first drawing process is completed, the die hole diameter is reduced in sequence to finally obtain flux-cored welding wire with a diameter of 1.0~1.2mm.
[0058] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use.
[0059] The welding wire prepared in Implementation Case 3 was used for butt welding of 2Mn18Al5SiMoTi test plates. After welding, metallographic observation specimens, tensile specimens, and high-temperature corrosion specimens were prepared. The test results are as follows: (1) The metallographic structure of the weld metal is a dual-phase structure of austenite + ferrite.
[0060] (2) The room temperature tensile test was carried out in accordance with GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Room temperature test method". The test results showed that the room temperature tensile strength of the butt joint was 722 MPa.
[0061] (3) The high temperature tensile test was carried out in accordance with GB / T 4338-2006 "Metallic Materials High Temperature Tensile Test Method". The test results showed that the tensile strength of the butt joint at 500℃ was 433MPa.
[0062] (4) A high-temperature corrosion test at 400℃ was conducted in accordance with GB / T 38430-2019 "Corrosion of metals and alloys - Isothermal exposure oxidation test method for metallic materials under high temperature corrosion conditions". A comparative test was conducted using 3Cr24Ni7SiNRE stainless steel. The test results showed that the high-temperature oxidation resistance of the cladding metal of the present invention is 1.71 times that of the base material 2Mn18Al5SiMoTi.
[0063] Example 4 Step 1: Weigh out the following components by mass percentage: Mn 42.0%, Al 10.5%, Cr 16.0%, Si 7.0%, Nb 1.2%, B 0.7%, Ti 0.9%, C 0.9%, Ce 1.1%, with the remainder being Fe. The sum of the mass percentages of the above components is 100%.
[0064] Step 2: Place the powder weighed in Step 1 into a vacuum heating furnace and heat it at 210℃ for 1.1 hours to remove the water of crystallization from the powder; place the dried powder into a powder mixer for thorough mixing for 1.1 hours. Step 3: Use alcohol to remove the grease from the surface of the 430 steel strip, and use a flux-cored wire drawing device to wrap the flux powder prepared in step 2 inside the 430 steel strip. The diameter of the first drawing die is 2.6mm. Step 4: After the first drawing process is completed, the die hole diameter is reduced in sequence to finally obtain flux-cored welding wire with a diameter of 1.0~1.2mm.
[0065] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use.
[0066] The welding wire prepared in Implementation Case 4 was used for butt welding of 2Mn18Al5SiMoTi test plates. After welding, metallographic observation specimens, tensile specimens, and high-temperature corrosion specimens were prepared. The test results are as follows: (1) The metallographic structure of the weld metal is a dual-phase structure of austenite + ferrite.
[0067] (2) The room temperature tensile test was carried out in accordance with GB / T 228.1-2021 "Metallic materials, tensile test - Part 1: Room temperature test method". The test results showed that the room temperature tensile strength of the butt joint was 720 MPa.
[0068] (3) The high temperature tensile test was carried out in accordance with GB / T 4338-2006 "Metallic Materials High Temperature Tensile Test Method". The test results showed that the tensile strength of the butt joint at 500℃ was 424MPa.
[0069] (4) A high-temperature corrosion test at 400℃ was conducted in accordance with GB / T 38430-2019 "Corrosion of metals and alloys - Isothermal exposure oxidation test method for metallic materials under high-temperature corrosion conditions". A comparative test was conducted using 3Cr24Ni7SiNRE stainless steel. The test results showed that the high-temperature oxidation resistance of the cladding metal of the present invention is 1.68 times that of the base material 2Mn18Al5SiMoTi.
[0070] Example 5 Step 1: Weigh out the following components by mass percentage: Mn 44.0%, Al 10.1%, Cr 15.5%, Si 6.1%, Nb 1.1%, B 0.75%, Ti 0.85%, C 0.95%, Ce 1.35%, with the remainder being Fe. The sum of the mass percentages of the above components is 100%.
[0071] Step 2: Place the weighed powder from Step 1 into a vacuum heating furnace and heat it at 201℃ for 1.2 hours to remove the water of crystallization from the powder; place the dried powder into a powder mixer for thorough mixing for 1.2 hours. Step 3: Use alcohol to remove the grease from the surface of the 430 steel strip, and use a flux-cored wire drawing device to wrap the flux powder prepared in step 2 inside the 430 steel strip. The diameter of the first drawing die is 2.6mm. Step 4: After the first drawing process is completed, the die hole diameter is reduced in sequence to finally obtain flux-cored welding wire with a diameter of 1.0~1.2mm.
[0072] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use.
[0073] The welding wire prepared in Implementation Case 5 was used for butt welding of 2Mn18Al5SiMoTi test plates. After welding, metallographic observation specimens, tensile specimens, and high-temperature corrosion specimens were prepared. The test results are as follows: (1) The metallographic structure of the weld metal is a dual-phase structure of austenite + ferrite.
[0074] (2) The room temperature tensile test was carried out in accordance with GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Room temperature test method". The test results showed that the room temperature tensile strength of the butt joint was 729 MPa.
[0075] (3) The high temperature tensile test was carried out in accordance with GB / T 4338-2006 "Metallic Materials High Temperature Tensile Test Method". The test results showed that the tensile strength of the butt joint at 500℃ was 428MPa.
[0076] (4) A high-temperature corrosion test at 400℃ was conducted in accordance with GB / T 38430-2019 "Corrosion of metals and alloys - Isothermal exposure oxidation test method for metallic materials under high-temperature corrosion conditions". A comparative test was conducted using 3Cr24Ni7SiNRE stainless steel. The test results showed that the high-temperature oxidation resistance of the cladding metal of the present invention is 1.63 times that of the base material 2Mn18Al5SiMoTi.
[0077] Example 6 Step 1: Weigh out the following components by mass percentage: Mn 49.0%, Al 11.9%, Cr 19.0%, Si 9.0%, Nb 2.9%, B 0.9%, Ti 1.1%, C 1.1%, Ce 1.4%, with the remainder being Fe. The sum of the mass percentages of the above components is 100%.
[0078] Step 2: Place the powder weighed in Step 1 into a vacuum heating furnace and heat it at 222℃ for 1.9 hours to remove the water of crystallization from the powder; place the dried powder into a powder mixer for thorough mixing for 1.8 hours. Step 3: Use alcohol to remove the grease from the surface of the 430 steel strip, and use a flux-cored wire drawing device to wrap the flux powder prepared in step 2 inside the 430 steel strip. The diameter of the first drawing die is 2.6mm. Step 4: After the first drawing process is completed, the die hole diameter is reduced in sequence to finally obtain flux-cored welding wire with a diameter of 1.0~1.2mm.
[0079] Step 5: After the flux-cored welding wire is drawn, it is wound onto the welding wire spool by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for later use.
[0080] The welding wire prepared in Implementation Case 6 was used for butt welding of 2Mn18Al5SiMoTi test plates. After welding, metallographic observation specimens, tensile specimens, and high-temperature corrosion specimens were prepared. The test results are as follows: (1) The metallographic structure of the weld metal is a dual-phase structure of austenite + ferrite.
[0081] (2) The room temperature tensile test was carried out in accordance with GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Room temperature test method". The test results showed that the room temperature tensile strength of the butt joint was 739 MPa.
[0082] (3) The high temperature tensile test was carried out in accordance with GB / T 4338-2006 "Metallic Materials High Temperature Tensile Test Method". The test results showed that the tensile strength of the butt joint at 500℃ was 445MPa.
[0083] (4) A high-temperature corrosion test at 400℃ was conducted in accordance with GB / T 38430-2019 "Corrosion of metals and alloys - Isothermal exposure oxidation test method for metallic materials under high-temperature corrosion conditions". A comparative test was conducted using 3Cr24Ni7SiNRE stainless steel. The test results showed that the high-temperature oxidation resistance of the cladding metal of the present invention is 1.77 times that of the base material 2Mn18Al5SiMoTi.
[0084] This disclosure presents a high-alumina heat-resistant steel welding wire for thermal power plants and its preparation method, which has the following advantages compared to the prior art: (1) The welding wire designed in this disclosure can form an austenite + ferrite dual-phase structure, which avoids the tendency of pure austenite welds to be prone to hot cracking, and also avoids the problem of high hot brittleness of pure ferrite structure.
[0085] (2) The welding wire disclosed herein forms a dense Al2O3-Cr2O3-rare earth oxide composite film on the weld surface through a composite alloying design, which significantly extends the service life of boiler pipes.
[0086] (3) The welding wire of this disclosure adds microalloying elements to inhibit grain growth and improve the high-temperature creep strength of the weld.
[0087] (4) The welding wire disclosed herein can replace nickel-based welding materials, which can reduce welding costs by more than 40%, and save more than 10 million yuan in material costs for a single million-kilowatt unit.
[0088] It is understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of this disclosure, and this disclosure is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and substance of this disclosure, and these modifications and improvements are also considered to be within the scope of protection of this disclosure.
Claims
1. A high-alumina heat-resistant steel welding wire for thermal power plants, characterized in that, The welding wire comprises: flux powder and welding wire coating, wherein, The powder comprises the following components by mass percentage: Mn 40.0-50.0%, Al 10.0-12.0%, Cr 15.0-20.0%, Si 6.0-10.0%, Nb 1.0-3.0%, B 0.6-1.0%, Ti 0.8-1.2%, C 0.8-1.2%, Ce 1.0-1.5%, with the remainder being Fe; The weld bead is made of 430 steel strip.
2. The high-alumina heat-resistant steel welding wire for thermal power plants according to claim 1, characterized in that, The particle size of the powder is 100-200 mesh.
3. The high-alumina heat-resistant steel welding wire for thermal power plants according to claim 1, characterized in that, The filling rate of the medicinal powder is controlled at 22-25%.
4. The high-alumina heat-resistant steel welding wire for thermal power plants according to claim 1, characterized in that, The thickness of the 430 steel strip is 0.3-0.5 mm, and the width is 6-8 mm.
5. The high-alumina heat-resistant steel welding wire for thermal power plants according to claim 1, characterized in that, In the butt welding of the high-alumina heat-resistant steel welding wire used in thermal power plants on a 2Mn18Al5SiMoTi test plate, a dense Al2O3-Cr2O3-rare earth oxide composite film is formed on the weld surface.
6. A method for preparing high-alumina heat-resistant steel welding wire for thermal power plants as described in any one of claims 1 to 5, characterized in that, The method includes: Weigh out the following components by mass percentage: Mn 40.0~50.0%, Al 10.0~12.0%, Cr 15.0~20.0%, Si 6.0~10.0%, Nb 1.0~3.0%, B 0.6~1.0%, Ti 0.8~1.2%, C 0.8~1.2%, Ce 1.0~1.5%, with the remainder being Fe, as the pharmaceutical powder. The medicinal powder is heated and then mixed. The welding wire is pretreated, and the mixed powder is wrapped in a 430 steel strip of the welding wire. After drawing, a high-alumina heat-resistant steel welding wire for thermal power plants is obtained.
7. The method according to claim 6, characterized in that, The temperature for heating the powder is 200~230℃, and the holding time is 1~2h.
8. The method according to claim 6, characterized in that, The processed powder should be mixed for 1-2 hours.
9. The method according to claim 6, characterized in that, The diameter of the high-alumina heat-resistant steel welding wire used in thermal power plants is 1.0~1.2mm.